SMOKING PROHIBITIONS AND THE IMPACT ON INDIVIDUALS IN OREGON (Tufts Archival Research Center, 2007)
Report by Savarese and Associates arguing against smoking prohibition in Oregon. Discusses the negative economic impacts of prohibition. Argues that prohibition will lead to increased class discrimination based on enforcement and the disproportionate number of poor people who smoke. Also implies that young people will be particularly targeted. Includes statistics on professions of smokers and age of Oregon smokers.